Les vestiges fauniques de la rue Lecointre à Reims/Durocortorum : une carrière utilisée comme dépotoir - Frédéric Poupon (Gallia)
The archaeological excavation carried out at 22 rue Lecointre in Reims/Durocortorum (Marne) has brought to light nearly 3,000 faunal remains from a former chalk quarry located on the northwestern outskirts of the ancient city of Durocortorum and which was used as a dumping ground at the end of the 3rd c. and the beginning of the 4th c. AD. The analysis of these remains illustrates the presence of an important variety of waste materials, primarily derived from the exploitation of animal products. A majority of them are associated with food production, represented by an abundance of pig remains (at the expense of goat remains), and associated with secondary waste materials, represented by poultry and game remains. Though we cannot confirm their consumption, in terms of wild fauna, bear and fallow deer are represented by rare remains. And while numerous within this faunal assemblage, the cattle bones collected here testify mainly to waste generated by two distinct activities. The first corresponds to a butchery activity illustrated by a surplus of vertebrae and foot bones (primal cut), followed by scapulae and ribs (secondary cut). The meat portions from these two bones (chuck steak, and short ribs) may have been subject to specific preparation techniques in the form of salting or smoking. Limb bones are under-represented, but also bear traces of secondary cutting, though many of them were subsequently and quite systematically recovered by bone craftsmen. The latter activity is characterized by the discarding of numerous diaphysis fragments, including the articular extremities, as well as metapod bones, associated with shaping waste and manufacturing failures discarded during the working of the bone material. Although the bone processing waste may very likely have come from the regular cleaning of nearby bone object crafting spaces (especially in rue Maucroix), the composition of the food waste material from the quarry, as well as the presence of butchery waste, stand out strongly amidst the faunal assemblages of the surrounding artisanal sites. The predominance of pork remains, whose preferential consumption appears to have been the prerogative of castrum residents, has no equivalent on the artisanal sites, wherein goat and beef were the preferred meats. Similarly, analysis of the anatomical distribution of bovine remains highlights the contrast between the abundance of butchery waste (vertebrae, ribs and shoulder or hip bones) on rue Lecointre and their deficit within nearby artisanal sites. As the quarry is situated in an outlying sector, undergoing rapid change, the atypical composition of the bone remains found therein raises the question of the origin of this waste material. The answer is likely to be found in the monumental ensembles near the quarry, such as the polygonal temple and the amphitheater, located, respectively, 50 and 120 m from the quarry. It is not uncommon for such faunal assemblages, especially for the remains of bovine butchery, to be attested to in the vicinity of performance sites or within the sanctuaries themselves. The preferential consumption of pork may also correspond to the remains of communal meals within the context of ritual or religious performances, or it may illustrate food goods brought to and enjoyed near the amphitheater. The close link, whether topographical or liturgical, between these two buildings precludes neither. The only examples discovered in recent years of bear and fallow deer bones, associated with these various waste types, are accumulated along the periphery of the amphitheater. This leaves little doubt –at least in the case of the bear remains– as to the provenance of these taxa (the amphitheater) and their likely correlation to venatio. Finally, in this case, the remains of equids, as well as those of dogs and cats, indicate corpse management that is perhaps more individual in nature. It is characterized by the discarding of bones from one or two individuals in a space dedicated to the dumping of waste produced by a variety of other activities. The rare equine bones that present cut marks are likely related to an incidental recovery of raw materials (hides, tendons, muscle, bones). These deposits are clearly different from the collective management of equine corpses previously observed in Reims, and characterized by the mass disposal of carcasses in one place and resulting in an exclusive and impressive dumping site for these remains.